Seasonal changes in sexual activity and semen quality in the Angora ram. 2. Semen volume, quality and freezability - Loubser, P.G.; Niekerk, C.H. van (1983)
Seasonal changes in semen volume and quality in the Angora ram were investigated. Semen was collected by means of an artificial vagina and criteria such as ejaculate volume, semen pH, sperm concentration, sperm motility, percentage live and normal sperm and survival of sperm after freezing and thawing were monitored. The Angora ram was found to be a seasonal breeder (late summer through autumn) and produced semen only during this period. Semen volume differed highly significantly (p